2011
DOI: 10.1029/2010jd014988
|View full text |Cite
|
Sign up to set email alerts
|

Consistency assessment of Atmospheric Infrared Sounder and Infrared Atmospheric Sounding Interferometer radiances: Double differences versus simultaneous nadir overpasses

Abstract: [1] Quantifying the radiometric difference and creating a calibration link between Atmospheric Infrared Sounder (AIRS) on Aqua and Infrared Atmospheric Sounding Interferometer (IASI) on MetOp are crucial for creating fundamental climate data records and intercalibrating other narrowband or broadband satellite instruments. This study employs two different methods to assess the AIRS and IASI radiance consistency within the four Geostationary Operational Environmental Satellite (GOES) imager infrared channels (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 22 publications
(29 reference statements)
1
38
0
1
Order By: Relevance
“…Both of the two hardware approaches achieve nearly the same spectral characteristics. Details on their calibration and performance are found in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Both of the two hardware approaches achieve nearly the same spectral characteristics. Details on their calibration and performance are found in [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The brightness temperatures are 25 stored in 2-byte integers using data packing (e.g., CF convention scale_factor and add_offsets). Brightness temperature noise is generally less than 0.25 K (Ellrod et al, 1998) which was later evaluated by Wang et al (2011) who found errors at night on the order of 0.15 K.…”
Section: Calibrationmentioning
confidence: 99%
“…Post-launch analysis has deemed IR calibration accurate to within 0.15 to 0.25 K (Ellrod et al, 1998;Wang et al, 2011). The visible calibration was provided by Inamdar and Knapp (2015), where the uncertainty is about 3% (in scaled reflectance units).…”
Section: Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Potential drawbacks of these SNOs are a limited dynamic range of measured radiances and problems in characterising scenes over bright snow-or ice-covered surfaces. Similar to Wang et al (2011), who applied double differencing to inter-calibrate infrared radiances of two polar-orbiting sounders, we explore the use of the SEVIRI instrument to transfer calibrations from one polar imager to another. In this way, MODIS-Terra as well as two Advanced Very High Resolution Radiometers (AVHRRs) are tied to MODIS-Aqua.…”
Section: J F Meirink Et Al: Solar Channel Inter-calibration Using mentioning
confidence: 99%